Development of Sagaurung Fish Downstream Potential as a form of Women’s Empowerment in order to increase family economic income - Fretty Welta; Sopian (International Journal of Business and Quality Research, 2025)
Community empowerment is an effort to make what belongs to the community better so that the community can fulfill its needs as well as possible so that it can survive and develop independently in the economic, religious, social and cultural fields. In this research, researchers took a community empowerment of MSMEs, household businesses, BUMDes, Farmer groups, markets and other community economic assistance as part of this program. This empowerment takes various forms, such as training, workshops, funding, equipment assistance, renovation of facilities/infrastructure, and so on. It is hoped that this approach will improve societal and economic welfare in economic terms, community empowerment focuses on areas of progress and increases public awareness of local resources that can be exploited to generate income. Community economic empowerment requires strengthening community members' ownership of factors of production, control over distribution and marketing, the ability to earn sufficient income, and the ability to access information, knowledge and skills.